Targeting ferroptosis, a novel programmed cell death, for the potential of alcohol-related liver disease therapy - Shi, Jing-Fen; Liu, Yu’e; Wang, Yan; Gao, Ru; Wang, Yi; Liu, Jun (Frontiers in Pharmacology, 2023)
Ferroptosis is a new iron-dependent cell death mode, which is different from the other types of programmed cell death, such as apoptosis, necrosis, and autophagy. Ferroptosis is characterized by a process in which fatal lipids from lipid peroxidation accumulate in cells and eventually lead to cell death. Alcohol-related liver disease (ALD) is a type of liver injury caused by excessive alcohol intake. ALD is a broad-spectrum disease category, which includes fatty liver, steatohepatitis, hepatitis, cirrhosis, and hepatocellular tumors. Recent studies have found that ferroptosis is involved in the pathological development of non-viral liver diseases. Therefore, ferroptosis may be an ideal target for the treatment of non-viral liver diseases. In this review article, we will elaborate the molecular mechanism and regulatory mechanism of ferroptosis, explore the key role of ferroptosis in the ALD process, and summarize the existing targeted ferroptosis drugs and their feasibility for the treatment of ALD.